Simulation of Performance of SURA Particle Detectors as an External Trigger - Maryam Alibakhsh; Gohar Rastegarzadeh (Iranian Journal of Astronomy and Astrophysics)
Semnan University Radio Array (SURA) with 4 LPDA antennas is recording the cosmic ray event on the roof of the University. As an external trigger, we are going to add three scintillator detectors to this array. In this work, by using CORSIKA code, simulation has been carried out for primary proton in the 100TeV-100PeV range of energies for different zenith angle. For these set of simulated shower reconstructed zenith angle and its uncertainty and core position are obtained and the effect of distance between the detectors on the zenith angle reconstruction investigated. Because the structure of the shower (thickness and curvature of the disk) affects the determination of the arrival direction, the angular resolution vs core distance is also studied. In addition, the study of the EAS hadronic cores is a useful tool to investigate the hadronic interaction models. We have shown that by increasing zenith angle and distance from the shower core, uncertainty increases.